2019
DOI: 10.1002/bdm.2125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rewarding medium effort and the role of sample size

Abstract: We take the point‐of‐view of designers of incentive systems who cannot reward the behavior they most desire, and must decide whether to reward a less desired behavior. For example, when it is difficult to distinguish between the desired high‐effort strategy from a low‐effort “mimicry” strategy, policy makers may choose instead to reward medium levels of effort. Experiments 1 and 2 examine situations in which participants (the subjects of the policy) base their decisions on personal experience obtained in 100 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…In addition, our results demonstrate that enforcement can be effective even if it does not use harsh punishments and does not reduce the expected return from reckless choices. When responsible behavior implies an efficient Nash equilibrium (the environment examined here), it is enough to ensure that the enforcement increases the probability that responsible behavior leads to the best possible payoffs toward 1 (to 0.95 in the current study, see similar observation in Erev et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…In addition, our results demonstrate that enforcement can be effective even if it does not use harsh punishments and does not reduce the expected return from reckless choices. When responsible behavior implies an efficient Nash equilibrium (the environment examined here), it is enough to ensure that the enforcement increases the probability that responsible behavior leads to the best possible payoffs toward 1 (to 0.95 in the current study, see similar observation in Erev et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…The current research also makes a theoretical contribution—extending the two‐sample model developed in Roth et al (see also Erev, Gilboa Freedman, & Roth, 2019) to multiple alternatives. Roth et al proposed the two‐sample model as a generalization of the basic one‐sample “reliance on small samples” model.…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, the best fit of the data is obtained with a much smaller sample size ( k = 1 or 2) than in other decisions‐from‐experience studies ( k = 9; Erev & Haruvy, 2016; Erev & Roth, 2014; Yakobi, Cohen, Naveh, & Erev, 2020). The smaller sample size was also found to best capture learning from the experience of others (Erev et al, 2019). Why this is so demands further investigation.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The attentive participants had similar checking rates as the inattentive participants (0.31 (SD = 0.32) and 0.29 (SD = 0.31), respectively). The relatively high checking rate indicated that participants were more sensitive to the typical outcome than to the high magnitude loss (e.g., Erev, Gilboa Freedman, & Roth, 2019). The learning curves (Figure 6, right panel) showed a similar pattern to Study 4A.…”
Section: Resultsmentioning
confidence: 62%